(untitled) (Emancipação, 2020)
The mediatization of politics is constituent of the political space of the democratic societies. There is a typical normative model which presents the relation of the organization and the economic activity of the press with politics and democracy through an analogy to the liberal conception of economy and politics. There is criticism to this model: the market pressures do not lead to the diversity of contents, pluralism and politicization. On the contrary, they tend to produce the depoliticization of the field of the journalism and, like this, the content homogenization and the restriction of the pluralism. Objective of this article: to put the problem to the Brazilian press and investigate 352 headlines about the Dilma government in the newspapers Folha de São Paulo, O Estado de São Paulo and O Globo. Content and framework analyses revealed a structure of homogeneity of the newspapers’ position in relation to the politics: lack of diversity to the public space. The mediatization of politics has meaning restrictions of the universe of the possible ones with negative unfolding for the democracy.